Nano-Carbon-Based Application of Parecoxib Sodium Combined with Hydromorphone in Preventing Anesthesia Hyperalgesia Caused by Remifentanil after Thyroidectomy: Parecoxib Sodium with Hydromorphone in Preventing Anesthesia Hyperalgesia - Zhou, Jianwei; Wu, Zhenhua; Xu, Hongtao; Gao, Lijuan; Wang, Chuanguang; Zheng, Fang; Yao, Yinguang (Cellular and Molecular Biology, 2022)
Nano-carbon is often used as a tracer in thyroidectomy, to improve the accuracy of the operation. Remifentanil is the most commonly used anesthetic during thyroidectomy, but the use of remifentanil can sometimes cause patients with anesthesia hyperalgesia. Therefore, auxiliary anesthetics are often used in surgery to prevent remifentanil from causing anesthesia hyperalgesia. The purpose of this article is to explore the specific application effect of the fusion agent of hydromorphone and parecoxib sodium after thyroidectomy based on nano-carbon in the prevention of remifentanil-induced anesthesia hyperalgesia. Taking 60 patients who underwent thyroidectomy based on carbon nanotechnology in our hospital as the research object, the patients were divided into the parecoxib sodium group, hydromorphone control group and hydromorphone and parecoxib sodium fusion agent group. All patients were injected with remifentanil before surgery for general paralysis. Ten minutes before the end of the operation, the parecoxib sodium group was injected with quantitative parecoxib sodium, and the hydromorphone control group was injected with quantitative hydromorphone, hydromorphone and the parecoxib sodium fusion medicament group was injected with a quantitative combination of parecoxib sodium and hydromorphone. The patient's comfort, calmness, pain, adverse reactions and recovery time of consciousness were counted. The results of the study showed that the sedation score of the hydromorphone and parecoxib sodium fusion drug group was (15.8±1.5), the pain degree score was (1.9±0.5), lower than the other two groups, and the postoperative recovery time was (38±5.0) )min, lower than the other two groups. It can be seen that the use of a fusion agent of hydromorphone and parecoxib sodium after thyroidectomy based on nano-carbon is effective in preventing and reducing remifentanil-induced anesthesia hyperalgesia.